A novel bacterium producing polyhydroxyalkanoates from palm oil mill effluent - Hassan, Mohd Ali; Zakaria @ Mamat, Mohd Rafein; Abd. Aziz, Suriani; Mohamad Ghazali, Farinazleen; Shirai, Yoshihito; Wakisaka, Minato (2009)
The bacterial strain EB 172, isolated from digester treating palm oil mill effluent, was investigated by polyphasic taxanomic approach. The cells were rod-shaped, Gram-negative, non-pigmented, non-spore-forming and non-fermentative. Phylogenetic analyses usnign the 16S rRNA gene sequence showed that the strains C. terrigena (96.8%), C. koreensis (93.4%), C. composti (92.9%), and C.kerstersii (91.1%). The ability of C. putranesis to produce polyhydroxyalkanoates (PHA) when supplied with organic acids made this bacterium is unique in Comamonas species. The bacterial strain was clearly distinguished from all of the existing strains using phylogenetic analysis, fatty acid composition data and a range of physiological and biochemical characteristics. The DNA G+C content of the genomic DNA was 59.1 mol%. It is evident from the genotypic and phenotypic data that strain Comamonas putranesis represents a novel species in the genus Comamonas, for which the name Comamonas putranesis sp. nov. is proposed.